MODEL PENGEMBANGAN MUTU PENDIDIKAN DALAM PERSPEKTIF EDWARD SALLIS - Fahrani, Diah Anika; Riswandi, Riswandi; Rini, Riswanti (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
The education quality development model is a systematic approach designed to enhance the quality of education within a learning institution. Its primary objective is to elevate the standards and effectiveness of teaching, thereby creating a more conducive learning environment for students, educators, and other stakeholders in education. Several widely employed models aim to enhance educational quality, including Total Quality Management (TQM), Plan-Do-Check-Act (PDCA), Six Sigma, the Malcolm Baldrige National Quality Award, and Edward Sallis. The main focus of this essay is to provide an in-depth definition and understanding of Edward Sallis and explore topics closely associated with the educational quality development model from his perspective.